Variable Sharing in Substructural Logics: an Algebraic Characterization - Badia, Guillermo (Bulletin of the Section of Logic, 2018)
We characterize the non-trivial substructural logics having the variable sharing property as well as its strong version. To this end, we find the algebraic counterparts over varieties of these logical properties.